Student Evaluation of Clickers in a Combined Dental and Dental Hygiene Periodontology Course. Issue 10 (1st October 2013) - Satheesh, Keerthana M.; Saylor‐Boles, Catherine D.; Rapley, John W.; Liu, Ying; Gadbury‐Amyot, Cynthia C.
Abstract : The purpose of this report is to describe the general use of clickers as an active learning tool and how they were used in teaching a combined periodontology course for second–year dental and junior dental hygiene students. A survey was used to capture student perceptions following completion of the course. Specific domains were active learning, improved performance, and expectations. The survey response rate was 94.5 percent (121/128). Descriptive analyses showed that, in the domain of active learning, 102 (84.3 percent) agreed/strongly agreed that the use of clickers made the lectures more interactive; sixty–six (54.5 percent) agreed/strongly agreed that the clickers made them focus; and ninety–two (76 percent) agreed/strongly agreed that the clickers encouraged active participation. In the domain regarding improved performance, sixty–three (52 percent) agreed/ strongly agreed that the review sessions utilizing clickers helped them prepare for tests. In the domain of expectations, ninety–three (76.9 percent) had a better idea of what to expect on the examination due to the use of clickers, and seventy–three (60.3 percent) thought that the clickers should be used in future semesters for this class. In addition, faculty members appreciated the greater participation afforded through the use of clickers to obtain a better understanding of the students' grasp of course content. Learning theory suggests that students must actively engage in the learning process in order for meaningful learning in the form of critical thinking and problem–solving to take place. In this study, students confirmed that the use of clicker technology encouraged their active participation in a periodontology course.